Phosphorylation by G1-specific cdk-cyclin complexes activates the nucleolar transcription factor UBF - Voit, Renate; Hoffmann, Manuela; Grummt, Ingrid (The EMBO journal, 1999)
Transcription of rRNA genes by RNA polymerase I increases following serum stimulation of quiescent NIH 3T3 fibroblasts. To elucidate the mechanism underlying transcriptional activation during progression through the G1 phase of the cell cycle, we have analyzed the activity and phosphorylation pattern of the nucleolar transcription factor upstream binding factor (UBF). Using a combination of tryptic phosphopeptide mapping and site-directed mutagenesis, we have identified Ser484 as a direct target for cyclin-dependent kinase 4 (cdk4)?cyclin D1- and cdk2?cyclin E-directed phosphorylation. Mutation of Ser484 impairs rDNA transcription in vivo and in vitro. The data demonstrate that UBF is regulated in a cell cycle-dependent manner and suggest a link between G1 cdks?cyclins, UBF phosphorylation and rDNA transcription activation.